Identification of "Streptococcus milleri" group isolates to the species level with a commercially available rapid test system. - Flynn, C E (1995)
Clinical isolates of the "Streptococcus milleri" species group were examined by conventional methods and a rapid, commercially available method for the identification of these strains to the species level. The levels of agreement between the identifications obtained with the commercially available system (Fluo-Card Milleri; KEY Scientific, Round Rock, Tex.) and conventional methods were 98% for 50 Streptococcus anginosus strains, 97% for 31 Streptococcus constellatus strains, and 88% for 17 isolates identified as Streptococcus intermedius. Patient records were also studied in order to gain information on the frequency and sites of isolation of each of the three "S. milleri" group species.